Evidence for Resilient Agriculture (ERA): Livestock Data - Rosenstock, Todd S.; Steward, Peter Richard; Joshi, Namita; Mumo, Elijah Musyoki; Ombewa, Babra Vivian Adhiambo; Kacha, Gabrielle Nour (2023)
A detailed meta-dataset describing the context, management and outcomes of livestock feed experiments from sub-Saharan Africa. The dataset geolocates experimental sites and records details of animal breeds, diet ingredients, their nutritional composition and digestibility, feed presentation and intake rates, and yield and production outcomes. Data from 405 peer-reviewed publications are included generating 10554 unique observations. The animals represented in the dataset are sheep (26.4% of observations), goat (19.5%), fish (15.4%), cattle (14.1%), chickens (13.6%), pigs (6.7%) and others (2.2%). The geographic scope of experimental locations includes Nigeria (20% of locations), Ethiopia (17.7%), South Africa (14.9%), Egypt (8.8%), Kenya (7%), Tanzania (5.8%), Ghana (4.2%) and 16 more countries (21.7%). The most commonly reported outcomes in the dataset are Meat Yield (28.9% of observations), Weight Gain (27.3%), Feed Conversion Ratio (16.8%), Variable Cost (6.8%), Protein Conversion Ratio (3.3%) and 31 other outcomes (16.7%). Nutritional composition data are available for 2153 animal diets or diet ingredients and digestibility data available for 870. A description of the fields in the dataset can be found in the Field_Description table.